Egg ultrastructure of two species of Galgupha Amyot & Serville, with a discussion of the eggs and oviposition patterns of thyreocorid and allied groups (Hemiptera: Heteroptera: Pentatomoidea: Thyreocoridae) - Matesco, Viviana Cauduro; Bianchi, Filipe Michels; Campos, Luiz Alexandre; Grazia, Jocelia (Zootaxa, 2012)
Immature stages are known in only 11 species of the Thyreocoridae. In this paper, the eggs of Galgupha (Euryscytus)difficilis (Breddin) and Galgupha (Gyrocnemis) fossata McAtee & Malloch are described and illustrated. Egg morphologyand oviposition habit in the Thyreocoridae and Cydnidae are reviewed. Adults of both species were collected in SãoFrancisco de Paula municipality, state of Rio Grande do Sul, Brazil, and maintained in the laboratory for oviposition. Theeggs were examined by stereomicroscopy and scanning electron microscopy and photographed. In G. (E.) difficilis, theeggs were laid singly or in pairs; each egg is cylindrical (0.8 x 0.5 mm) and white and the chorion is shiny, translucent,and smooth; the micropylar processes (2–4) are short and stalked. In G. (G.) fossata, the eggs were laid singly; each eggis cylindrical (0.9 x 0.6 mm) and white and the chorion is shiny, translucent, and granulated; the micropylar processes (4–10) are short, stalked, and transversely constricted. The eggs of both species are similar to those of other thyreocorids,especially of other corimelaenines. The Thyreocoridae in the broadest sense (including the Parastrachiinae) is not auniform group concerning egg morphology, oviposition behavior, and maternal care. Within the Pentatomoidea, based onegg morphology, the Cydnidae is the group nearest to the Thyreocoridae. The evolution of the eggs in the Pentatomoidea should be investigated within a phylogenetic framework, including egg characters, in future cladistic analyses.